Pengaruh Lama Pengukusan terhadap Kualitas Kerupuk Singkong (Manihot esculenta Crant) - Nur Asril Yuda Fajrudin; Marianus Mayolis (Agriculture - Jurnal Ilmu Pertanian, 2026)
Cassava is an annual food crop in the form of a shrub, which has other names, namely cassava, cassava, grows in tropical and subtropical regions. If seen from the nutritional content of cassava, it contains 157.00 mg of calories, 0.80 g of protein, 0.30 g of fat, 37.90 mg of carbohydrates, 33.00 mg of calcium, 40.00 mg of phosphorus, 0.70 mg of iron, 385.00 SI of Vitamin A, 0.06 mg of Vitamin B1, 30.00 mg of vitamin C, 60.00 g of water and 75.00% of the edible part. In the processing of cassava crackers, generally people do not pay attention to the manufacturing process, especially the steaming process with the right length of time for the best results. Therefore, in this study, researchers pay more attention to the appropriate steaming process to see its effect on the quality of cassava crackers. The purpose of this study was to examine the effect of steaming time on the quality of cassava crackers so that it can provide good quality cassava crackers. This study was conducted in february 2026 and took place in the Laboratory of the Faculty of Agriculture, Nusa Nipa University, Maumere and the analysis of the Feed Chemistry Laboratory of the Faculty of Animal Husbandry, Nusa Cendana University, Kupang. The research method used a completely randomized design (CRD) with 5 treatments and 4 replications, so that 20 experimental units were obtained, with steaming times of 30 minutes, 60 minutes, 90 minutes, 120 minutes, 150 minutes. If there is an effect of the treatment, it is continued with the Least Significant Difference (LSD) test. The results of the study showed that the treatment of cassava crackers steaming time did not significantly affect the water content, ash content, color, and crispness, while the steaming time affected the fat, carbohydrate, protein, and taste levels. The best quality of the five treatments was in treatment 5 (P5), which was steamed for 150 minutes with a protein content test value of 1.77, ash content value of 4.15, carbohydrate value of 78.91, and color test value of 2.48. While the lowest quality was in treatment 1 (P1) with a steaming time of 30 minutes with a protein test value of 1.46, a taste test value of 2.02, a color test value of 1.69, and a crispiness test value of 2.2.6.